2013
DOI: 10.1083/jcb.201302095
|View full text |Cite
|
Sign up to set email alerts
|

In vitro reconstitution of an mRNA-transport complex reveals mechanisms of assembly and motor activation

Abstract: The budding yeast SHE mRNA-transport complex dimerizes to activate processive RNA transport, irrespective of the presence of RNA cargo, and multimerizes upon binding RNAs with multiple localization elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 59 publications
(171 reference statements)
1
48
1
Order By: Relevance
“…26 In addition, metal-shadowed electron microscopic images obtained with equimolar concentrations of mRNA, Myo4p and She2p, showed that zip codes are required for recruitment of Myo4p to localizing transcripts, and that up to eight motor heads can bind to the native four zip code ASH1 mRNA. 15 In agreement, Heym et al 20 also conclude that the vast majority of zip code elements in the cell are bound to motor complexes. Multiple zip codes are not essential for cellular mRNA localization, but their presence offers advantages by enhancing both the percentage of cells with correct mRNA localization, and the quality of localization at the bud tip.…”
Section: Conflicting Viewpointssupporting
confidence: 56%
See 3 more Smart Citations
“…26 In addition, metal-shadowed electron microscopic images obtained with equimolar concentrations of mRNA, Myo4p and She2p, showed that zip codes are required for recruitment of Myo4p to localizing transcripts, and that up to eight motor heads can bind to the native four zip code ASH1 mRNA. 15 In agreement, Heym et al 20 also conclude that the vast majority of zip code elements in the cell are bound to motor complexes. Multiple zip codes are not essential for cellular mRNA localization, but their presence offers advantages by enhancing both the percentage of cells with correct mRNA localization, and the quality of localization at the bud tip.…”
Section: Conflicting Viewpointssupporting
confidence: 56%
“…Subsequent to our publication, 15 a single molecule study by Heym et al 20 drew several conclusions contradictory to ours. They concluded that She2p alone is necessary for Myo4p to undergo processive motion, and that neither mRNA nor zip codes are necessary.…”
Section: Conflicting Viewpointscontrasting
confidence: 43%
See 2 more Smart Citations
“…Dimerization is regulated by the availability of cargo (4)(5)(6). However, cargo does not bind directly to Myo4p.…”
mentioning
confidence: 99%